An illustration of human sperm morphology and their functional ability among different group of subfertile males. (29th June 2018) - Sunanda, P.; Panda, B.; Dash, C.; Padhy, R. N.; Routray, P.
Summary: Condensed sperm chromatin is a prerequisite for natural fertilization. Some reports suggested the prevalence of chromatin condensation defects in teratozoospermia cases with head anomalies; conversely, earlier studies exemplified its occurrence in morphologically normal spermatozoa too. The aim of this study was to compare the condensation defects in correlation with head anomalies among different groups of subfertile males and its impact on the rate of fertilization in assisted reproduction procedures. Ultrastructure analysis of spermatozoa through scanning electron microscopy and atomic force microscopy could facilitate an in‐depth evaluation of sperm morphology. Nuclear condensation defects (%) in spermatozoa were analyzed in 666 subjects, and its effect on the rate of fertilization was analyzed in 116 IVF and 90 intracytoplasmic sperm injection cases. There was no correlation of condensation defects with head anomalies (%). Student's t ‐test showed no significant changes in mean values of condensation defects in abnormal semen samples in comparison with the normal group. Condensation defects were observed in normal spermatozoa too, which was negatively associated with the rate of fertilization in IVF ( p  <   0.01), but intracytoplasmic sperm injection outcome remained unaffected. Ultrastructure study revealed sperm morphological features in height, amplitude, and three‐dimensional views in atomic force microscopy images presenting surface topography, roughness property of head, and compact arrangement of mitochondria over axoneme with height profile at nanoscale. In pathological forms, surface roughness and nuclear thickness were marked higher than the normal spermatozoa. Thus, percentage of normal spermatozoa with condensation defects could be a predictive factor for the rate of fertilization in IVF. From diverse shapes of nucleus in AFM imaging, it could be predicted that defective nuclear shaping might be impeding the activity of some proteins/ biological motors, those regulate the proper Golgi spreading over peri‐nuclear theca.